Revitalizing Ibn Khaldun's Theory of Islamic Education for the Contemporary World - Husnul Amin; Yudi Pratama; Afifah Husnul Amin (STAI Hubbulwathan Duri, 2023)
Ibn Khaldun is a prominent Islamic intellectual figure. His thoughts on education refer to the development of science. His great thoughts about education are contained in his book “al- Muqodimmah”. Education, according to him, should instill piety, ethics, and a sense of social responsibility in learners, In this regard, Islamic education serves as a means to produce morally upright individuals who can positively impact their communities and discuss about Ibn Khaldun theory in modern world. The purpose of this study is to explain several theories of Islamic education according to Ibn Khaldun and explain the theory relevant to society’s needs. And the method used is a literature study with a historical approach. The conclusion, Ibn Khaldun's theory of Islamic education highlights the importance of a comprehensive approach that integrates religious, intellectual, and social dimensions. His theory emphasizes the cultivation of moral values, critical thinking, and the integration of Islamic teachings with other branches of knowledge. By following Ibn Khaldun's principles, Islamic education can serve as a transformative force, producing individuals capable morally upright and socially responsible to their societies at large.